Can molecular hydrogen supplementation enhance physical performance in healthy adults? A systematic review and meta-analysis - Zhou, Kaixiang; Shang, Zhangyuting; Yuan, Chaoqun; Guo, Zhenxiang; Wang, Yubo; Bao, Dapeng; Zhou, Junhong (Frontiers in Nutrition, 2024)
Background: Physical exertion during exercise often leads to exceeded oxidative stress and inflammatory responses, significantly affecting the physical performance. Current strategies to mitigate these effects are limited by effectiveness and potential side effects. Molecular hydrogen (H₂) has gained attention for its antioxidant and anti-inflammatory properties. Studies have suggested that H2 supplementation contributes to antioxidant potential and anti-fatigue during exercise, but variance in the observations and study protocols is presented across those studies. Objective: This review aims to comprehensively characterize the effects of H₂ supplementation on physical performance, providing knowledge that can inform the strategies using H2 for enhancing physical performance. Methods: We conducted a literature search of six databases according to the PRISMA guidelines. The data were extracted from the included studies and were converted into the standardized mean difference (SMD). After that, we performed random-effects meta-analyses and used the I2 statistic to evaluate heterogeneity. The GRADE was used to assess the quality of evidence obtained from this meta-analysis. Results: Twenty-seven publications consisting of 597 participants were included. The search finally included aerobic endurance, anaerobic endurance, muscular strength, lower limb explosive power, rating of perceived exertion (RPE), blood lactate (BLA), and average heart rate (HRavg) in the effect size (ES) synthesis. The ES of H2 on aerobic endurance, including V̇O2max (SMD=0.09, p=0.394; I2=0%), aerobic endurance exercise (SMD=0.04, p=0.687; I2=0%), were not significant and trivial; the ES of H2 on 30s maximal anaerobic endurance (SMD=0.19, p=0.239; I2=0%) was not significant and trivial; the ES of H2 on muscular strength (SMD=0.19, p=0.265; I2=0%) was not significant and trivial; but the ES of H2 on lower limb explosive power (SMD=0.30, p=0.018; I2=0%) was significant and small. In addition, H2 reduces RPE (SMD=-0.37, p=0.009; I2=58.0%) and BLA (SMD=-0.37, p=0.001; I2=22.0%) during exercise, but not HRavg (SMD=-0.27, p=0.094; I2=0%). Conclusions: These findings suggest that H2 supplementation is favorable in healthy adults to improve lower limb explosive power, alleviate fatigue, and boost blood lactate clearance, but may not be effectively improving aerobic and anaerobic endurance and muscular strength.